The Impact of Population, Labor, Unemployment, and Poverty on Economic Growth Regencies/Municipality in Sulawesi Tengah Province - Mubarak, Muhammad Syahrul; SBM, Nugroho (Pusat Pengkajian Ekonomi dan Kebijakan Publik, 2020)
High population growth could be a serious barrier to regional economic development. In general, if productivity in each sector of the economy is very low, there will be a high unemployment level in that society. The purpose of this study is to analyze the partial and simultaneous influences of population, labor, unemployment, and poverty on economic growth. The type of data used is panel statistic data from 11 regencies and municipality in Sulawesi Tengah province of Indonesia during the 2011-2019 period with 99 observations. The regression model with fixed effect approach was used to analyze the data panel. The results reveal that labor and unemployment do not significantly affect economic growth, whereas population and poverty significantly affect economic growth in positive and negative ways, respectively. The partial results of the test imply that the increase in population must be coherently supported by the specialization of the workforce through an increase in the length of school each individual. These implications can be realized through the construction of educational infrastructure. Poverty reduction can be implemented through the improvement of the education level of the people. It is expected that good education will generate more new experts to increase industrial productivity, which in turn will increase the output